2010
DOI: 10.1785/0120090179
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Earthquake Ruptures: Different Nucleation Strategies in a Dynamic Model with Slip-Weakening Friction

Abstract: The introduction of the linear slip-weakening friction law permits the solution of the elastodynamic equation for a rupture that develops on a fault by removing the singularity in the components of stress tensor, thereby ensuring a finite energy flux at the crack tip. With this governing model, largely used by seismologists, it is possible to simulate a single earthquake event; but, in the absence of remote tectonic loading, it requires the introduction of an artificial procedure to initiate the rupture (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…Hence, dynamic rupture simulations often adopt artificial nucleation procedures. Several studies have revealed that details of rupture initiation can significantly affect the subsequent rupture propagation [Festa and Vilotte, 2006;Shi et al, 2008;Lu et al, 2009;Bizzarri, 2010]. Here we assess the role of nucleation conditions in determining the rupture style by studying systematically the influence of the size of nucleation.…”
Section: Nucleation Proceduresmentioning
confidence: 99%
“…Hence, dynamic rupture simulations often adopt artificial nucleation procedures. Several studies have revealed that details of rupture initiation can significantly affect the subsequent rupture propagation [Festa and Vilotte, 2006;Shi et al, 2008;Lu et al, 2009;Bizzarri, 2010]. Here we assess the role of nucleation conditions in determining the rupture style by studying systematically the influence of the size of nucleation.…”
Section: Nucleation Proceduresmentioning
confidence: 99%
“…Within this zone, the friction coefficient is gradually reduced from its static to its dynamic value over a specified time of 0.5 s [Bizzarri , 2010]. Outside this zone, forced rupture is smoothly overtaken by spontaneous rupture.…”
Section: Frictional Propertiesmentioning
confidence: 99%
“…Interestingly, our numerical tests reveal that fully elastic simulations can partially emulate the reference simulation when increasing the critical slip distance D c . In this case, moment-release rate and rupture transfer dynamics are preserved, but exhibit slower rupture speeds and longer delays when transferring to adjacent segments due to an increased critical size [e.g., Ampuero et al, 2002;Bizzarri , 2010;Galis et al, 2014] to initiate self-sustained rupture by dynamic triggering.…”
Section: The Effect Of Off-fault Plasticity On the Ssd Rupture Transmentioning
confidence: 99%
“…The governing model assumed here (equation (10)) does not allow for a description of the hardening stage of the fault, unlike other friction models [e.g., Ruina, 1983;Sone and Shimamoto, 2009]. As thoroughly discussed in Bizzarri [2010a], to simulate the ongoing rupture propagation it is necessary to initially impose the nucleation, which is obtained by initially forcing the rupture to enlarge at a constant rupture speed (which equals to 2.4 km/s in our simulations). Also the breakdown stress drop is imposed in the nucleation patch; Dt b = t u À t f = 57.24 MPa.…”
Section: Fully Spontaneous Modeling Of Lubricated Faults: Constant Thmentioning
confidence: 99%